1998
DOI: 10.1097/00005344-199801000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Platelets, Macrophages, and Lipoproteins in Hypercholesterolemia: Antiatherogenic Effects of HMG-CoA Reductase Inhibitor Therapy

Abstract: To assess the effect of 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitors on plasma cholesterol concentrations and on platelet aggregation, lovastatin or fluvastatin, 40 mg daily, was given to hypercholesterolemic patients. After 24 weeks, plasma low-density lipoprotein (LDL) cholesterol concentrations were reduced by 37% after lovastatin therapy and 29% after fluvastatin therapy. The platelet cholesterol/phospholipid ratio was reduced by 33% and 26%, respectively. Platelet aggregation was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(65 citation statements)
references
References 34 publications
5
59
0
1
Order By: Relevance
“…45 Moreover, several recent studies have demonstrated beneficial effects of statin therapy on platelet function and fibrinolysis in hypercholesterolemic individuals. [45][46][47][48][49][50][51] Our findings, by contrast, demonstrate that statins inhibit platelet activation independent of serum cholesterol levels by upregulation of type III NOS. Therefore, our data may have direct clinical implications: eNOS upregulation may be the mechanism of protection in patients with average cholesterol levels, as observed in large statin trials.…”
Section: Discussionmentioning
confidence: 67%
“…45 Moreover, several recent studies have demonstrated beneficial effects of statin therapy on platelet function and fibrinolysis in hypercholesterolemic individuals. [45][46][47][48][49][50][51] Our findings, by contrast, demonstrate that statins inhibit platelet activation independent of serum cholesterol levels by upregulation of type III NOS. Therefore, our data may have direct clinical implications: eNOS upregulation may be the mechanism of protection in patients with average cholesterol levels, as observed in large statin trials.…”
Section: Discussionmentioning
confidence: 67%
“…On the other hand, P-selectin, though it may be derived from either platelets and/or endothelium [20], has potential as a new marker of platelet activation [21]. Platelet activity is enhanced in hypercholesterolaemia and may be a crucial factor in the pathogenesis of atherosclerotic lesion formation, and at least partially in the occurrence of cardiovascular events [22]. Activated platelets tend to aggregate and are found close to atherosclerotic plaques [23].…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Hydroxy metabolites of atorvastatin, but not the parent compound, inhibit oxidation of both LDL and very-low-density lipoprotein as well as high-density lipoprotein. 23 In addition, the hydroxy metabolites, representing 70% of active atorvastatin in plasma, demonstrate free radical-scavenging abilities that may contribute to inhibition of lipoprotein oxidation.…”
Section: Antioxidant Effectsmentioning
confidence: 99%